Aprovação no vestibular como sucesso escolar : as contribuições de um cursinho popular - Siqueira, Marina Hakime Contini de (2012)
The work herein was produced as a result of a research which aimed at understanding how access to higher education is provided for public school students. It sought to point out roads to success through Cursinho Alpha a preparation course for entrance exam , in which young people from public schools can succeed in entrance exams from public universities in the State of São Paulo. We discussed the means of obtaining this success achieved by eight students. Four students who attended Cursinho Alpha and other four students who did not attend it were interviewed. That choice on the subjects is due to the possibility of knowing the preparation roads of young people to achieve the considered synonym of success in our society: joining a renowned public university. The sustained hypothesis was that Cursinho Alpha, through their selection process, works with students who already had a good education and upbringing, which would help in achieving academic success . Supported by Pierre Bourdieu s concepts on the volume of cultural, social and economic capital which may trigger social classification/reclassification and Bernard Lahire s on the family influence on the education of youth. We sought, through the interviews, to delimit which were the real influences that led young people to success. Through interviews we may confirm our hypothesis and question ourselves about the selective process carried out by Cursinho Alpha and the extent to which students from public secondary education and who enter the public higher education can be considered as belonging to the common peoples